Comprehensive Study of Si-Based Compounds in Selected Plants (Pisum sativum L., Medicago sativa L., Triticum aestivum L.) - Aleksandra Orzoł; Edith Cruzado-Tafur; Adrian Gołębiowski; Agnieszka Rogowska; Paweł Pomastowski; Ryszard J. Górecki; Bogusław Buszewski; Małgorzata Szultka-Młyńska; Katarzyna Głowacka (Molecules, 2023)
This review describes the role of silicon (Si) in plants. Methods of silicon determination and speciation are also reported. The mechanisms of Si uptake by plants, silicon fractions in the soil, and the participation of flora and fauna in the Si cycle in terrestrial ecosystems have been overviewed. Plants of Fabaceae (especially Pisum sativum L. and Medicago sativa L.) and Poaceae (particularly Triticum aestivum L.) families with different Si accumulation capabilities were taken into consideration to describe the role of Si in the alleviation of the negative effects of biotic and abiotic stresses. The article focuses on sample preparation, which includes extraction methods and analytical techniques. The methods of isolation and the characterization of the Si-based biologically active compounds from plants have been overviewed. The antimicrobial properties and cytotoxic effects of known bioactive compounds obtained from pea, alfalfa, and wheat were also described.